Reanalysis of summer pressure systems affecting Iran\'s atmosphere - mahdi khazaei (تحقیقات کاربردی علوم جغرافیایی)
This study investigates the subtropical anticyclones and summer monsoons of the north hemisphere in the 500 hPa level, effective on Iran in a 38-year period (1975-2012). For this purpose, the data of geopotential heights of 500 hPa at 12 UTC with a spatial resolution of 2 by 2 degrees of the (NCEP/NCAR) were used. Results show that three independent patterns (Azores anticyclone, Saudi anticyclone and North West Africa anticyclone) and four combinatory patterns derived from the independent patterns have controlled the atmosphere of 500 hPa level of Iran. In most cases, the maximum in geopotential heights in above-mentioned anticyclone centers reach to more than 5920 geopotential meters, but often the tongue of these anticyclones control the atmosphere of 500 hPa levels of Iran with the geopotential height of 5880 to 5900 meters. In contrast, at this pressure level, the large-scale monsoon system is very weak and the maximum geopotential height of this system is about 5840 meters. The extent and intensity of the monsoon system has been reduced so that its tongues do not affect the 500 hPa level of Iran at any time. Given that the main factor in the development of large-scale monsoon system is the surface heating (bottom-up formation) and the main factor in the development of subtropical anticyclone is descending of atmospheric dynamics, the main reason for the development of summertime subtropical dynamic anticyclone should be a very strong and unit agent, something other than the summer monsoons.